The Evolution Of Islamic Pedagogy Studies: A Scientometric And Co-Citation Analysis - Hera Hapsari Kusuma; Benny Prasetiya; Febry Suprapto; Khoiriyah Khoiriyah (PT. Caesarindo Triloka Persada, 2026)
In the last decade, Islamic pedagogy has experienced significant growth as an academic field integrating spiritual, ethical, and digital dimensions. This study aims to examine the evolution, structure, and research front of Islamic pedagogy studies through a scientometric and co-citation analysis using Scopus-indexed data from 2012–2025. Employing the PRISMA 2020 protocol, data were systematically collected and analyzed with Bibliometrix (R) and VOSviewer to map publication trends, author collaboration networks, and thematic structures. The findings reveal an accelerating trend of publications after 2020, with Malaysia, Iran, and the United States as leading contributors. Thematic mapping identifies four major research clusters Islam evolution science, theology education, digital religion, and interfaith epistemology representing a paradigm shift toward integrative and transdisciplinary Islamic knowledge. The study highlights the growing role of digitalization, social constructionism, and ethical frameworks in shaping modern Islamic education. Novelty emerges in redefining the Islamization of knowledge through data-driven and empirical approaches that merge classical epistemology with contemporary science and technology. This research contributes methodologically by applying scientometric tools to Islamic studies, and conceptually by proposing a new transdisciplinary Islamic epistemology that bridges theology, ethics, and digital learning. The study serves as a foundation for evidence-based policy and future directions in global Islamic education research.